Internet Of Things (IoT) Based Soil Leveling and Compaction Prototype - Muhammad Fahrul Amin; Wahyu Dirgantara; Yandhika Surya Akbar Gemilang (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2024)
The purpose of this research is to design a prototype of a soil leveling and compaction tool based on the Internet of Things (IoT). Currently, many projects still rely on manual tools for soil leveling and compaction, which can result in reduced effectiveness, lack of safety for workers, and high levels of fatigue. Therefore, this tool is equipped with ESP32-Cam, DC Motor, and BTS 7960 Motor Driver, and will be operated remotely via a smartphone's Android remote control, utilizing IoT technology to enhance efficiency and accuracy in soil leveling and compaction. By three trials result on sandy soil showed a more significant reduction, with an average of 3.6 mm in 4 seconds, compared to rocky soil, which had an average reduction of 3.3 mm in 5.3 seconds over three trials.